The unified model description of order-disorder and displacive structural phase transitions - Stamenkovic, S. (Condensed Matter Physics, 1998)
A series of co-authors’ studies [1-7] devoted to the unified model description of structural phase transitions (SPT) in ferroelectrics and related materials are reviewed and partly innovated. Starting from a general Hamiltonian of pair-coupled anharmonic (quartic) oscillators, together with the concept of local normal coordinates, a unified model description of both order-disorder and displacive types of SPT-systems is proposed. Within the framework of the standard variational procedure, a hybridized pseudospin-phonon Hamiltonian is formulated by introducing variables corresponding to phonon, magnon-like(flipping) and nonlinear(domain–wall-like) displacements of atoms participating in SPT. This is achieved by representing the cooperative atomic motion onto several quasiequilibrium positions (in the simplest case, two) as slow tunnelling displacement (decomposed into magnon-like and soliton-like deviations), in addition to comparatively fast phonon oscillations around inhomogeneous momentary rest positions, in turn induced by domain–wall-like (soliton) excitations. The qualitative and quantitative analyses show that SPT (of the first or second order) can be either of a displacive (governed by a phonon soft mode), order-disorder (governed by a tunnelling–magnon-like soft mode) or of a mixed type, depending on both the coupling energy between atoms and their zero-point vibrational energy. In the critical temperature region, the domain–wall-like excitations bring on the formation of microdomains (precursor clusters of the ordered phase) which induce SPT of the Ising type universality class. The incomplete softening of the phonon or pseudomagnon mode occurs and a central peak due to slow cluster relaxation appears in the spectral density of excitations. Зроблено огляд і часткове оновлення серії робіт автора з співавторами [1-7], присвяченої уніфікованому модельному опису структурних фазових переходів (СФП) у сегнетоелектриках та споріднених матеріалах. Виходячи з загального гамільтоніану попарно зв’язаних ангармонічних (четвірних) осциляторів та враховуючи концепцію локальних нормальних координат, запропоновано уніфікований модельний опис систем з СФП обидвох типів: порядок-безпорядок і зміщення. В рамках стандартної варіаційної процедури формулюється гібридизований псевдоспін-фононний гамільтоніан введенням змінних, що відповідають фононним, магноно-подібним (з переворотом) і нелінійним (типу доменної стінки) зміщенням атомів, що беруть участь у СФП. Це досягається представленням колективного руху атомів через декілька квазірівноважних положень (в найпростішому випадку - двох) як повільного тунельного зміщення (розбитого на магноноподібні і солітоно-подібні відхилення) додатково до порівняно швидких фононних осциляцій навколо неоднорідних миттєвих положень спокою, в свою чергу індукованих збудженнями типу доменної стінки (солітонами). Якісний і кількісний аналізи показали, що СФП (першого чи другого роду) можуть бути типу зміщення (керованих м’якою фононною модою), порядок-безпорядок (керованих тунельною магноноподібною м’якою модою) чи змішаного типу залежно як від енергії зв’язку між атомами, так і від їхньої нульової точки коливної енергії. В області критичної температури збудження типу доменної стінки приводять до утворення мікродоменів (кластерів впорядкованої фази), які індукують СФП класу універсальності Ізінгівського типу. Має місце неповне пом’якшення фононної чи псевдомагнонної моди і у спектральній густині збуджень виникає центральний пік, викликаний повільною релаксацією кластерів.